ALLOPHONIC VARIATIONS AS STYLE MARKER OF A VOICE ACTOR - Donal Fernado Lubis; Diana Anggraeni (Jurnal Penelitian Humaniora, 2022)
This study deals with the allophones of several phonemes pronounced by a voice actor in performing a character in animation movie. It concerns with the stylistic analysis in phonetic and phonology levels that reinforce the voice actor in performance. The data are taken from the utterances spoken by Adam Sandler, the voice actor of Count Dracula in Hotel Transylvania-2. The method of data analysis is through descriptive qualitative based on stylistic and phonetic approaches. By comparing the general American accent with the voice actor’s pronunciation, it is found that the acoustic features  of  [5],  [r],  [?],  [º],  [n̪]  and  phonemes  /@/  and  /e/  have  particular  effects  in reinforcing the character in the movie, mainly to bring up comical atmosphere.Keywords: stylistics, phonetics, phonemes, allophones, voice actor